Education 4.0: The Students’ Perspectives toward the Use of Instagram in English for Survival Class - Endah Ratnaningsih (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Almost everyone today has an Instagram account which is used for posting and sharing status, news, and information. This study presents the students’ perspectives toward the use of Instagram in English for Survival Class. A case-study is conducted to obtain the data. Twenty-nine students of English for Survival Class are involved as the participants in this study. The results of the study show the advantages and the obstacles of the use of Instagram in the English for Survival Class. The findings of this study show the participants have positive perspectives about the implementation of Instagram in their class. Moreover, nothing is perfect but the main point is to provide the students with opportunities to explore their ability.